KONSEP NAFS (JIWA) DALAM ALQURAN - Teuku Wildan (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2017)
This article discusses the nafs (soul) in the Qur'anic Perspective. The concept of the Qur’an regarding the best nafs is to refer to the human side in a potentially good way, resulting in good behavior. In the sense of a positive nafs who can always control himself from his desires to goodness. Not a few verses in the Qur’an that encourage humans to maintain the sanctity of lust and not dirty it. And it can be concluded that humans are endowed with nafs by Allah, with the nafs that humans can live to function as they should. With nafs, man works. And with the nafs is human worship